Extracurricular Handball Achievement Development at SMP Negeri 1 Juwana, Pati District - Vidaliya Rizki Apriliana; Rumini (Universitas Negeri Semarang, 2025)
This study aims to provide an in-depth analysis of the performance development process in handball extracurricular activities at the junior high school level, specifically at SMP Negeri 1 Juwana, Pati Regency. Utilizing a qualitative descriptive approach, data were collected through in-depth interviews, direct observations, and documentation studies involving coaches and the school principal. Data analysis was conducted using the Miles and Huberman model to explore the dynamics of coaching comprehensively. The study population includes all individuals directly involved in the handball extracurricular program, such as coaches, students/athletes, extracurricular coordinators or physical education teachers, and the school principal. The findings reveal that the coaching activities are being carried out, though the quality and intensity vary. Most of the training still focuses on mastering basic techniques. Student enthusiasm and coach dedication emerge as key supporting factors in the process. Nevertheless, the study also identifies several significant challenges, including limited facilities and infrastructure, insufficient time and funding allocation, and a lack of local competitions. These factors hinder the full realization of students’ performance potential. Despite these obstacles, the coaching program contributes positively to students' character development. As a follow-up, the study recommends improvements in facilities, increased training hours, enhanced coach competencies, stronger collaboration with stakeholders, and greater financial support.